HUBUNGAN ANTARA JENIS KELAMIN, UMUR, DAN AKTIVITAS FISIK DENGAN DIABETES MELITUS TIPE 2 PADA LANSIA DI PUSKESMAS BALARAJA KABUPATEN TANGERANG - Rosita Rosita; Devi Angeliana Kusumaningtiar; Ahmad Irfandi; Ira Marti Ayu (Jurnal Kesehatan Masyarakat (Undip), 2022)
Type 2 diabetes mellitus is the most common type of diabetes accounting for 90% of all diabetes in the world is type 2 diabetes mellitus. Indonesia is ranked 7th out of 10 countries in the world. From health service data, the prevalence of people with type 2 diabetes mellitus has increased with a prevalence of 14.47% in 2019. This study aims to determine the relationship between sex, age, and physical activity with type 2 diabetes mellitus in the elderly at the Balaraja Health Center, Tangerang Regency. Methods This study used a cross sectional design. Sampling for respondent data uses the two-proportion difference test formula, and the number of samples obtained is 189 respondents. The sampling method used was random sampling with a systematic random sampling technique. The results showed that 76.2% did not suffer from type 2 diabetes mellitus, female 56.1%, elderly (60+ years) 66.7%, and high physical activity 89.9%. Based on the bivariate analysis using the chi-square test, there was a relationship between sex (p = 0.012) and age (p = 0.046) with type 2 diabetes mellitus, and there was no relationship between physical activity (p = 1000) and type 2 diabetes mellitus. This study can be concluded that there is a relationship between sex and age with type 2 diabetes mellitus, and there is no relationship between physical activity and type 2 diabetes mellitus. Physical activity is a protective factor against the incidence of type 2 diabetes mellitus.